Highly shape‐selective Zn‐P/HZSM‐5 zeolite catalyst for methanol conversion to light aromatics. (15th July 2020) - Jia, Yanming; Wang, Junwen; Zhang, Kan; Ding, Chuanmin
Abstract : A highly shape‐selective and relatively long‐lifetime HZSM‐5‐based catalyst (Zn‐2P/HZSM‐5) was prepared by chemical modification with both ZnSiF6 ·6H2 O and H3 PO4 solution. The phosphoric acid modification could effectively modulate the Brønsted acid strength of the HZSM‐5 catalyst, which promotes the oligomerization, alkylation, cyclization, and hydrogen transfer reactions. The introduction of Zn‐Lewis acid sites significantly improved the dehydroaromatization of higher olefins. All of these were very beneficial for the generation of BTX (i.e. b enzene, t oluene, and x ylene) hydrocarbons in aromatization of methanol. The coke amount and the average rate of coke formation decreased over the Zn‐2P/HZSM‐5 catalysts, which may largely be ascribed to its lower strong acid sites and lower outer surface acidity. The catalytic performance of methanol aromatization showed that the Zn‐2P/HZSM‐5 catalyst exhibited the highest BTX selectivity of about 46.76% and the longest catalytic lifetime of about 498 h at T = 400 °C, P = 0.1 MPa, and weight hourly space velocity = 0.7 h −1 . Abstract : Partially strong acid sites of HZSM‐5 are changed into weak acid sites after H3 PO4 modification, which effectively promotes the oligomerization, alkylation, cyclization, and hydrogen transfer reactions. The Zn‐Lewis acid sites could improve the dehydroaromatization reaction. The Zn‐2P/HZSM‐5 catalyst exhibits higher BTX (i.e. b enzene, t oluene, and x ylene) selectivity and longer catalyst lifetime in the MTA reaction.